BRICs & clicks: Insights into the sociomateriality of consuming social networking sites - Lichy, Jessica; Khvatova, Tatiana; de Oliveira, Mauro (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
This study addresses the lack of comparative research on the consumption of social networking sites (SNS) and SNS user behaviour in four emerging economies: Brazil, Russia, India, China. Using online survey and interviews, data are collected from individuals in order to identify different types of SNS user behaviour. From the findings, we develop a simplified framework of digital culture to show the effects of BRIC cultural context on sociomaterial context, and how these factors can be used to explain SNS user behaviour. The findings offer contemporary insights that can inform businesses operating in BRIC markets for leveraging digital interactivity.